Peminatan Mahasiswa Sistem Informasi UINSU 2023 Terhadap Organisasi HMI, UKOMI, LPM, dan LDK - Amira, Nurul; Dara, Esti Kurnia; Hamzah, Muhammad; Rifaldi, Tengku Khairul; Firzatullah, Iqbal; Nasution, Adelyna Oktavia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research analyzes the interest of students from the 2023 cohort of the Information Systems Study Program at State Islamic University of North Sumatra (UINSU) toward student organizations HMI, UKOMI, LPM, and LDK. Using a quantitative descriptive method with an online survey approach, the research involved 51 student respondents. Data were collected through questionnaires and analyzed using descriptive statistics and chi-square tests. The results showed a low level of student participation in student organizations, with 84.3% of respondents being inactive, and academic focus being the main reason for inactivity at 52.1%. The chi-square test indicated no significant relationship between gender and organizational activity (p-value = 0.50699), suggesting that academic factors and competency development more dominantly influence organizational decisions. Among active students, HMI was the most popular organization 87.5%, with soft skill development as the primary motivation 50%. There was potential interest 68% in organizations directly related to the field of information systems. This research recommends developing leadership training programs and information technology skills integrated with the academic curriculum to increase student participation